Optimizing Hydroponically Cultivated Kale Growth Using Nano-Formulated Organic Fertilizers: A Multivariate Evaluation Using PCA - Resti Fevria; Vauzia Vauzia; Silvy Annisa; Santi Diana Putri; Roni Jarlis (Journal of Applied Agricultural Science and Technology, 2026)
Kale (Brassica oleracea var. acephala) cultivated in hydroponic systems commonly relies on inorganic AB Mix nutrients, which raises sustainability concerns. This study evaluated the potential of nano-technology liquid organic fertilizers (nano-POC) derived from Sargassum, Gliricidia sepium (gamal leaves) and Tithonia diversifolia as partial substitutes for AB Mix in hydroponic kale cultivation. The experiment was conducted using different substitution formulations, and plant growth responses were assessed based on morphological and biomass-related parameters. The results showed that partial substitution of AB Mix with nano-POC maintained superior growth performance compared to full organic application. The formulation P3S (50% AB Mix + 50% Sargassum nano-POC) produced the most balanced and consistent growth responses, reaching a plant height of 22.5 cm, an average of seven leaves and a dry weight of 0.17 g, and showed no significant difference from the 100% AB Mix control. In contrast, the exclusive use of nano-POC resulted in significant declines across all growth indicators. Multivariate analysis using Principal Component Analysis (PCA) confirmed the stability and consistency of the optimal treatment across growth parameters. These findings indicate that nano-POC functions effectively as a complementary nutrient source in hydroponic systems. Integrating nano-technology liquid organic fertilizers through partial substitution strategies offers a sustainable approach to reducing dependence on synthetic fertilizers while maintaining hydroponic kale productivity.